2007
DOI: 10.1007/s11199-007-9360-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sex Diversity in Sport Organizations: Introduction to a Special Issue

Abstract: The purpose of this paper is to introduce the Special Issue on gender and sex diversity in sport organizations. In doing so, we first provide a brief outline of the extant literature, emphasizing the research and theoretical developments at the macro, meso, and micro level of analysis. Based on this framework and review, we allude to the communalities and intricacies in the existing understanding of sex and gender in the sport workplace. Further, we highlight how the contributions in the Special Issue address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 49 publications
1
46
1
Order By: Relevance
“…Given the masculine context of U.S. intercollegiate athletics (Burton et al in press;Cunningham and Sagas 2008;Whisenant et al 2002), it is noteworthy that we did not find support for Hypotheses 2 a-c. Instead, we found that participants did not prefer male leaders to female leaders when evaluating associated leadership outcomes.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Given the masculine context of U.S. intercollegiate athletics (Burton et al in press;Cunningham and Sagas 2008;Whisenant et al 2002), it is noteworthy that we did not find support for Hypotheses 2 a-c. Instead, we found that participants did not prefer male leaders to female leaders when evaluating associated leadership outcomes.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, intercollegiate athletics continues to be sexsegregated following traditional gender and sex-role stereotyping with men in more senior leadership positions and women represented in more subordinate and less powerful positions Sartore and Cunningham 2007;Tiell and Dixon 2008). Overall, women are underrepresented in intercollegiate athletics, marginalized to particular roles, and paid less for their work (Cunningham and Sagas 2008). Hence, as propositioned by role congruity theory, a prejudice may exist against potential female leaders in intercollegiate athletics because leadership ability is more generally ascribed to men who exhibit agentic qualities, than to women who display more communal characteristics (Eagly and Karau 2002).…”
Section: Role Congruity Theory-evaluation Of Female Leadersmentioning
confidence: 99%
“…Among these career positions and others, researchers have adopted a myriad of theoretical perspectives to examine the underrepresentation of women in leadership positions in sport (cf. Cunningham and Sagas 2008). The summation of these works reaffirms that the power and privilege accorded to men and masculinity in sport continues to marginalize women at nearly every level.…”
Section: Role Modelingmentioning
confidence: 87%
“…Dealing with socially and historically constructed effects of dominant masculine practices seems to be a part of women's everyday condition in male-dominated institutions (Cunningham and Sagas 2008). While traditional practices may be highly influential, they may be changed by individuals willing to create alternative knowledge about gender power structures that are taken for granted.…”
Section: Introductionmentioning
confidence: 99%